Sistem Penadaan Musik Tradisi Sasak Rebana Lima - Hari Murcahynto; Alwan Hafiz; Rona Ika Febrian (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
The purpose of this research is to describe the funding system used by Tambourine Lima. This type of research uses a qualitative descriptive method. Data collection techniques with data triangulation techniques, namely observation, interviews, and data collection with documents. The data analysis used consisted of four stages, namely data collection, data reduction, data presentation, and data verification. The results of the study show that the Tambourine Lima tuning system uses a pentatonic scale, namely the tone 2-3-5-6-2. In the Rebana Lima marking system, it starts from a low 2 tone and ends with a high 2 tone and does not use a 1 tone. The conclusion of the research is that in Tambourine Lima to produce the notes in each musical instrument, the player must adjust his left hand to produce the right tone and according to his tuning. each player holds a musical instrument, and is beaten according to the song being played to produce harmony. Keywords: Rebana lima, Tone system, Traditional Music